Giant claw reveals the largest ever arthropod - Braddy, Simon J (The Royal Society, 2007)
The fossil record has yielded various gigantic arthropods, in contrast to their diminutive proportions today. The recent discovery of a 46 cm long claw (chelicera) of the pterygotid eurypterid (‘sea scorpion’) Jaekelopterus rhenaniae, from the Early Devonian Willwerath Lagerstätte of Germany, reveals that this form attained a body length of approximately 2.5 m—almost half a metre longer than previous estimates of the group, and the largest arthropod ever to have evolved. Gigantism in Late Palaeozoic arthropods is generally attributed to elevated atmospheric oxygen levels, but while this may be applicable to Carboniferous terrestrial taxa, gigantism among aquatic taxa is much more widespread and may be attributed to other extrinsic factors, including environmental resources, predation and competition. A phylogenetic analysis of the pterygotid clade reveals that Jaekelopterus is sister-taxon to the genus Acutiramus, and is among the most derived members of the pterygotids, in contrast to earlier suggestions.